Structural rearrangements affect blastocyst development - Wang, Yizi; Ma, Yuanlin; Tan, Yanling; Wang, Jing; Pan, Jiafu; Song, Junli; Wang, Yali; Xu, Yanwen (Archives of gynecology and obstetrics, 2025)
It is disputable whether chromosomal translocations lead to an inferior embryo development. The purpose of this study was to evaluate whether structural rearrangements (SR) affect blastocyst formation as compared to monogenic disorders in preimplantation genetic testing (PGT) cycles. A total of 791 PGT-SR cycles and 757 PGT-M cycles from January 2021 to May 2023 were included. Lower blastocyst formation (graded 3BB or higher) rate was detected in the PGT-SR group compared with the control PGT-M group. In addition, lower proportion of day 5 blastocysts was found in the PGT-SR group compared with the control PGT-M group. Overall, a comparatively 12.7% lower proportion of eligible blastocysts in PGT-SR cycles. As expected, there were fewer balanced/normal blastocysts for transfer in the PGT-SR group (balanced/normal blastocysts rate, 32.3 vs. 59.9%, P = 0.02). The estimated curve by inverse model showed that yields of transferrable balanced/normal blastocyst per cycle came to a plateau stage followed with a rapid rise once the oocytes retrieved reached to the number of 20.4 in PGT-M cycle and 28.3 in PGT-SR cycle respectively. Our results demonstrated that patients with SR had a high chance of obtaining lower blastocyst development and significantly fewer usable blastocysts available for transfer compared to PGT-M in their first ovarian stimulation cycle.